2012
DOI: 10.1086/663195
|View full text |Cite
|
Sign up to set email alerts
|

Are Gastropods, Rather than Ants, Important Dispersers of Seeds of Myrmecochorous Forest Herbs?

Abstract: Seed dispersal by ants (myrmecochory) is widespread, and seed adaptations to myrmecochory are common, especially in the form of fatty appendices (elaiosomes). In a recent study, slugs were identified as seed dispersers of myrmecochores in a central European beech forest. Here we used 105 beech forest sites to test whether myrmecochore presence and abundance is related to ant or gastropod abundance and whether experimentally exposed seeds are removed by gastropods. Myrmecochorous plant cover was positively rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Traveset et al [39], however, showed that it can lead to species regression and in the long term, even to local extinctions. As shown by Türke et al [40], gastropods appear to substitute ants as seed dispersers in Central European beech forests. Interestingly, these forests are still inhabited by the native large slugs A. rufus and A. ater (L.) whereas A. lusitanicus is still absent (personal observation by M.Türke).…”
Section: Discussionmentioning
confidence: 80%
“…Traveset et al [39], however, showed that it can lead to species regression and in the long term, even to local extinctions. As shown by Türke et al [40], gastropods appear to substitute ants as seed dispersers in Central European beech forests. Interestingly, these forests are still inhabited by the native large slugs A. rufus and A. ater (L.) whereas A. lusitanicus is still absent (personal observation by M.Türke).…”
Section: Discussionmentioning
confidence: 80%
“…In a recent study by Türke et al (2010) slugs were identified as seed dispersers of forest myrmecochores [11]. In these habitats, benefits of gastropodochory for the plant could potentially be greater dispersal distances permitted by gastropods than by ants [11], the availability of gastropods as seed dispersers where ants are rare [12] or it may reduce the subsequent risk of seed predation as diaspores swallowed and defecated by slugs were less attractive to rodents than untreated diaspores in the laboratory [11]. Furthermore, gut passage through slugs can even accelerate seed germination or increase total germination [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Gastropod-defecated seeds were, in general, undamaged and germinable and thus dispersed endozoochorously [11], [13], [14], [18], [19]. A recent study highlighted the importance of gastropods for the removal of myrmecochorous diaspores in beech forests in Germany [12], which is particularly interesting as myrmecochores were also highly abundant where ants were rare or missing, suggesting that gastropods might substitute ants as seed dispersers in certain habitats. Also in the field gastropods often left diaspores behind with their elaiosomes being detached [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most arable plant species, however, lack obvious adaptations for dispersal and rely on gravity when shedding their seeds 4 , which permits very limited dispersal distances unless seeds are transported by man 3 . Recent research highlights the importance of so far Renewable Agriculture and Food Systems: Page 1 of 4 doi:10.1017/S1742170512000415 underappreciated invertebrate taxa, in particular, gastropods 5 and earthworms 6 in the dispersal of seeds of herbs. Also in crop fields or adjacent wild flower strips, gastropods were responsible for the removal of a fair proportion of weed or herb seeds 7,8 .…”
Section: Introductionmentioning
confidence: 99%